Impact of an increase in excise tax levied on alcohol on reducing drunken driving in Durban (Kwazulu-Natal) - Sikwela, Misery M; Aderemi, Timothy A (Asian Development Policy Review, 2025)
This study investigated the nexus between the increase in excise tax levied on alcohol and the reduction in drunken driving in Durban (KwaZulu Natal). The study approach was quantitative, and 203 respondents were selected using the convenience sampling method. The respondents were interviewed using a semi-structured questionnaire, which was conducted through surveys to solicit their views, opinions, and perceptions about the role of excise tax in reducing accidents. The study reveals that an increase in excise tax is an important factor influencing alcohol consumption among adults in South Africa. The study shows that people are reluctant to reduce or switch to low-priced alcohol when the tax is increased. Alcohol, to them, has been used as a toxicant to relax and have fun, and it was not important for them to understand the consequences of alcohol consumption despite an increase in excise tax or an increase in the price of alcohol. Increments in the total price of alcohol can lead to a reduction in drinking and driving and its aftermath effects within all age groups. Therefore, the study recommends that public transport must be improved to accommodate people who want to move around Durban without causing harm to other innocent road users.